Motivational Profiles in Unemployment: A Self-Determination Perspective - Leoni van der Vaart; Anja Van den Broeck; Anja Van den Broeck; Sebastiaan Rothmann; Hans De Witte; Hans De Witte (Frontiers Media S.A., 2022)
In general, being unemployed has negative implications for the individual and the mental health of the public as a collective. One way to escape this situation is to search for a job. However, following self-determination theory (SDT), unemployed people's different reasons (i.e., their motivation) for engaging in a job search influence their well-being, attitudes, and behaviors for better or worse. Some research has already supported the associations between different types of motivation and these outcomes, but less is known about how these types of motivation simultaneously associate with these outcomes. The current study addressed this issue by studying how different motivational profiles had different implications for the affective experiences, commitment to employment, and job search behavior of the unemployed. Latent profile analysis, among 865 unemployed individuals from previously disadvantaged communities in South Africa, highlighted four distinct motivational profiles: motivated, ambivalent, amotivated, and unmotivated. The motivated reported some good well-being (i.e., positive experiences) and economic outcomes (i.e., employment commitment and job search), but these came at a cost (i.e., more negative experiences). The same went for the ambivalent, but to a lesser extent. Being unmotivated seemed to have the opposite effect in that it came with psychological benefits, but with economic costs, as these individuals might withdraw from the labor market. This also applied to the amotivated, although they experienced less psychological benefit than their unmotivated counterparts. The findings made several contributions to SDT and unemployment research and could help tailor interventions and policies for particular types of unemployed people.